3(х -2,9)=6,9 как сделать

3(х -2,9)=6,9 как сделать
Гость
Ответ(ы) на вопрос:
Гость
3(x-2,9)=6,9 3x-8,7=6,9 3x=15,6 x=5,2
Гость
                                                                                        3(х -2,9)=6,9 1)Раскрываем скобки:                                                   3х - 8,7 =6,9 2) Приводим подобные слагаемые, получаем:           3х = 6,9 +8,7 3) Считаем:                                                                    3х =15,6 4) Находим х:                                                                 х= 15,6 : 3                                                                                           х=5,2
Не нашли ответ?
Ответить на вопрос
Похожие вопросы